EXPLORING THE MAJOR CHALLENGES OF WOMEN-LED STARTUPS IN INDIA: A FOCUS ON BENGALURU, KARNATAKA - Tharamani S; Bhavani V. L (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study investigates the key challenges faced by women entrepreneurs in launching and sustaining startups in India, with a specific focus on Bengaluru, Karnataka. Despite the city's vibrant startup ecosystem, women-led ventures continue to encounter systemic barriers, including limited access to funding, gender bias, lack of mentorship, complex regulatory frameworks, and work–life balance struggles. Utilizing primary data collected from 335 women entrepreneurs, the research applies descriptive statistics and Likert-scale analysis to highlight critical impediments across various dimensions of entrepreneurial engagement. The findings underscore the urgent need for inclusive financial systems, targeted mentorship, safer work environments, and enabling infrastructure to support women entrepreneurs. Policy implications and recommendations are also discussed to enhance gender equity in the entrepreneurial landscape.